A Study on Equivalent Circuit Model of RF Discharge Based on Multi-Physics Field - Xinkai Fu; Fei Dai; Ruitao Hu, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Belongs to EMC problems, the equivalent circuit model of RF discharge is studied. By establishing the correlation between circuit parameters of equivalent circuit and plasma characteristics, this paper conducts a brief analysis on the RF discharge mechanism with different frequencies.